Stakeholder Pressure, External Assurance, Firm Size, And Sustainability Report - Anudya Dhiya Shabiihah; Sari Andayani (UNIVED Press, 2025)
This study aims analyze the impact of stakeholder pressure, use of external assurance, and size of the company on the quality of the sustainability report disclosure on the company go public. The data used in this study are secondary data obtained from the annual financial statements and stand alone sustainability reports of companies listed on the Indonesian Stock Exchange for 2019-2022. The analysis method used was a double linear regression analysis with the help of SPSS 25. The results showed that environmental pressure, investor pressure, the use of external assurance, and the size of the company had a positive impact on the quality of the sustainability report disclosure.